Key factors for successful implementation of the National Rollover Protection Structure Rebate Program: A correlation analysis using the consolidated framework for implementation research - Tinc, Pamela J; Jenkins, Paul; Sorensen, Julie A; Weinehall, Lars; Gadomski, Anne; Lindvall, Kristina (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVES ': 'On US farms, tractor overturns are the leading cause of death; however, these fatalities are preventable with the use of a rollover protection structure (ROPS). A ROPS rebate program was established in New York in 2006 to address these fatalities. Due to its success, the program expanded to six additional states before being implemented as the National ROPS Rebate Program (NRRP) in 2017. The aim of this study was to evaluate the success of the NRRP implementation using short- and long-term ROPS outcome measures and identify which components of the consolidated framework for implementation research (CFIR) correlate with these outcomes. ' ' METHODS ': 'Stakeholders involved in the NRRP implementation were surveyed at four time points, beginning at the time of the NRRP launch and then every six months. These surveys measured 14 relevant CFIR constructs. Correlations between CFIR survey items (representing constructs) and three outcome measures (intakes, funding progress, and retrofits) were used to identify CFIR survey items that are predictive of the outcomes. ' ' RESULTS ': 'Eight CFIR survey items were highly correlated (rho ≥0.50) with at least one of the three outcome measures. These eight CFIR survey items included four constructs: access to knowledge and information, leadership engagement, engaging (in fundraising and funding requests), and reflecting and evaluating. ' ' CONCLUSIONS ': 'The results of this study provide important guidance for continuing the implementation of the NRRP. Similarly, these findings can inform the evaluation of other similarly structured implementation efforts and the application of CFIR in a variety of settings.
Keywords: agriculture; consolidated framework for implementation research; correlation analysis; factor; implementation; National Rollover Protection Structure Rebate Program; occupational safety; rollover; safety; scale-up; stakeholder engagement